Makna Simbolik “Popene’e” Pada Prosesi Pernikahan Etnik Tialo di Kabupaten Parigi Moutong: Kajian Semiotik - Fauzan, Arfan; Yunidar, Yunidar; Sukma, Sukma (Ranah: Jurnal Kajian Bahasa, 2025)
The purpose of this research is to describe the forms of symbolic meaning and the functions of symbolic meaning in the "popene'e" wedding procession of the Tialo ethnic group. The research method used in this study is descriptive qualitative, with data collection techniques including observation, interviews, recording, note-taking, and documentation. As for the data analysis technique using Miles and Huberman's theory, it involves data collection, data reduction, data presentation, and conclusion. Based on the research findings, the "Popene'e" procession consists of eight main stages: (1) welcoming the bride and groom; (2) peeling, splitting coconuts, cutting and splitting wood; (3) slicing banana leaves; (4) stepping on the tray; (5) bringing kitchen utensils and cooking bananas; (6) praying for well-being; (7) feeding each other; and (8) shaking hands. Meanwhile, the results related to the symbolic meaning in this procession are divided into two: verbal meaning (in the form of mantras/ganes) and nonverbal meaning (through tools and equipment). Overall, these symbols reflect the hope for responsibility, harmony, fertility, and protection in family life. The functions of this traditional procession include (1) communication; (2) knowledge and cultural inheritance; (3) mediation with ancestors and God; and (4) social participation. Abstrak Tujuan penelitian ini untuk mendeskripsikan bentuk makna simbolik dan fungsi makna simbolik pada prosesi pernikahan “popene’e” Etnik Tialo. Metode penelitian yang digunakan dalam kajian ini adalah deskriptif kualitatif dengan teknik pengumpulan data observasi, wawancara, perekaman, pencatatan, dan dokumentasi. Adapun Teknik analisis data menggunakan teori Miles dan Huberman yaitu pengumpulan data, reduksi data, penyajian data, dan kesimpulan. Berdasarkan hasil penelitian bentuk prosesi “Popene’e” terdiri dari delapan tahapan utama: (1) monyambute nu pungantinge (menyambut pengantin); (2) monimbaluse, mombiase niuge kangkai mongkolge, mombiasi ayu (mengupas, membelah kelapa dan memotong, membelah kayu); (3) monesege longu pensae (mengiris daun pisang); (4) mongunjae baki (menginjak baki); (5) mongkoni alatu wahu jopa monjaane pensae (membawa alat dapur dan memasak pisang); (6) mondo’a salamate (doa selamat); (7) mepea’anane (saling menyuap); dan (8) mondasi (jabat tangan). Sedangkan hasil terkait makna simbolik dalam prosesi ini terbagi menjadi dua, yaitu makna verbal (berupa mantra/gane) dan makna nonverbal (melalui alat dan perlengkapan). Secara keseluruhan, simbol-simbol ini merefleksikan harapan akan tanggung jawab, kerukunan, kesuburan, dan perlindungan dalam kehidupan berumah tangga. Fungsi dari prosesi adat ini mencakup (1) fungsi komunikasi; (2) fungsi pengetahuan dan pewarisan budaya; (3) fungsi mediasi dengan leluhur dan Tuhan; serta (4) fungsi partisipasi sosial.